Sistema automático de aproveitamento de águas das chuvas para uso doméstico e irrigação - Oliveira, Kauann Jacome de (Universidade Federal Rural do Semi-Árido, 2019)
This work presents a low cost automation prototype for rainwater harvesting systems as well as its use for a household irrigation system with a man-machine interface. The designed system is implemented with a 328p ATMega micro controller, used in arduino boards a prototyping platform. As results are presented the time charts for the automatic control rules and in order to prove the veracity of the proposed system, where a plywood model was made and also have a control center where the human-machine interface (HMI) allowing the user to interact with the whole system, allowing manual control of the system. Given these results, it is possible to contribute to the environment by reducing the use of drinking water for less noble purposes, thus contributing to the reduction of expenses and to the reduction of accumulation in urban areas, thus avoiding the risk with floods.
Automatic rainwater harvesting system for domestic use and irrigation
Monografia
Keywords: Automação residencial; Microcontroladores; Sistemas automáticos; Sistemas embarcados; Reaproveitamento de águas.; Home automation; Microcontrollers; Automatic systems; Embedded systems; Water reuse; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA